Factors Affecting Patient Safety Culture And Medical Error Prevalence In Emergency Services - Tuğba Çınarlı; Zeliha Koç; Hızır Ufuk Akdemir; Celal Katı (Association of Nurse Managers, 2020)
Emergency service is a unit where necessary precautions are taken in order to prevent health condition of a person who has a health problem due to any reason to worsen and which has unique working conditions. Emergency service is a very complex unit with high patient load when compared with other units of the hospital. Emergency units accept patients with the need of acute care. On the other hand situations such as the high quantity of the patients in the emergency service and low quantity of the healthcare professionals, crowdedness of the working environment, communication insufficiency, problems with teamwork, interruption of the activities and assignment of multiple missions threaten patient safety and may increase tendency for medical errors.